2015
DOI: 10.1016/j.electacta.2015.03.209
|View full text |Cite
|
Sign up to set email alerts
|

Direct Methanol Anion Exchange Membrane Fuel Cell with a Non-Platinum Group Metal Cathode based on Iron-Aminoantipyrine Catalyst

Abstract: The objective of the current report is to compare the performance of poly(phenylene) based anion exchange membranes in an alkaline direct methanol fuel cell when platinum cathode catalysts are replaced with non-platinum cathode catalysts. In a KOH-free methanol fuel, we show that a less expensive non-Pt cathode catalyst (derived from Fe-Aminoantipyrine, Fe-AAPyr, using Generations 1 and 2 sacrificial silica supports) provide better or comparable performance to commercial Pt cathode catalysts. The peak power de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Nitrogen is considered to be an essential component for the formation of an active site in the catalyst for ORR. 6,[12][13][14][19][20][21][22] Several studies have reported the performance of the single DMFC operation utilizing the Fe-and Co-based catalysts as the cathode. One is the two-electron transfer pathway resulting in the H 2 O 2 production, whereas the other is the four-electron transfer pathway, which directly produces H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is considered to be an essential component for the formation of an active site in the catalyst for ORR. 6,[12][13][14][19][20][21][22] Several studies have reported the performance of the single DMFC operation utilizing the Fe-and Co-based catalysts as the cathode. One is the two-electron transfer pathway resulting in the H 2 O 2 production, whereas the other is the four-electron transfer pathway, which directly produces H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in Figure C, in the presence of NaOH, the efficiency of DyFNRs‐PdNPs‐MWCNT catalyst‐based MEA was improved. According to the literature, the higher performance arises from an adequate source of OH − ions that is essential for oxidation of methanol and diminished anode over potential . The highest value of anodic current and power density in optimum concentration of CH 3 OH and NaOH were 18 mA cm −2 and 4.4 mWcm −2 , respectively.…”
Section: Examination Of Fuel Cell Efficiencymentioning
confidence: 99%
“…As shown in Figure (C) In the presence of NaOH, Fe 3 O 4 HNS‐PdPtAuNPs catalyst based MEA demonstrated improved performance. As illustrated in the literature, this enhancement in efficiency could be related to enough supply of OH − ions required for methanol oxidation and reduced anode overpotential . The maximum current density and peak power density for 1 M methanol and 1 M NaOH were 34 mA cm −2 and 5.44 mW cm −2 , respectively.…”
Section: Evaluation Of Fuel Cell Performancementioning
confidence: 99%